Global uncertainties: security in an Africa of networked, multi-level governance - Leonard, David (UK Data Service, 2014)
The programme of research centres on how the various institutions responsible for the production of security and the management of conflict in Sub-Saharan African societies do, could and should evolve in response to the presence of violent conflict. These institutions include: the armed forces, police, courts (civil as well as criminal), 'traditional' institutions of local governance, elections (and other methods of choosing leadership), international organisatoins (such as the United Nations, African Union, UN High Commission for Refugees, the World Court,), and the community of international donor nations. The programme is built on the observation that all governance (especially in Africa) is multi-leveled and networked - from the village to the international organisation, and well beyond what is specified in formal government structures. Thus the focus will be not only on the ways in which key conflict-management institutions evolve themselves but also on the changing ways in which the networks in which they are embedded actually operate. This leading edge research challenges theories about the state, state formation, and sovereignty as well as the dynamics of violent conflict as presented in the dominant current work on Africa. The primary methods of research will be network analysis and qualitative interviewing.